A global bibliometric and visualized analysis of the links between the autophagy and acute myeloid leukemia - Gao, Yao; Wu, Zhenhui; Chen, Yingfan; Shang, Guangbin; Zeng, Yingjian; Gao, Yue (Frontiers in Pharmacology, 2024)
Background and objectives: Autophagy is a cellular process where damaged organelles or unwanted proteins are packaged into a double-membrane structure and transported to lysosomes for degradation. Autophagy plays a regulatory role in various hematologic malignancies, including acute myeloid leukemia (AML). However, there are few bibliometric studies on the role of autophagy in AML. The purpose of this study is to clarify the role of autophagy in acute myeloid leukemia through bibliometric analysis. Methods: The literature on autophagy and AML research from 2003 to 2023 was searched in Web of Science Core Collection, and bibliometric tools such as VOSviewer 1.6.18, Cite Space (6.1.R3), RStudio (R package bibliometrix), and Scimago Graphica were used to understand the current status and hotspots of autophagy and AML research. The study conducted an analysis of various dimensions including the quantity of publications, countries, institutions, journals, authors, co-references, keywords, and to predict future development trends in this field by drawing relevant visualization maps. Results: A total of 343 articles were obtained, published in 169 journals, written by 2,323 authors from 295 institutions in 43 countries. The journals with the most publications were Blood and Oncotarget. China had the most publications, and Chongqing Medical University and Sun Yat-sen University had the most publications. The author with the highest number of publications was Tschan, Mario P. The main types of research included clinical research, in vitro experiments, in vivo experiments, public database information, and reviews, and the forms of therapeutic effects mainly focused on genetic regulation, traditional Chinese medicine combination, autophagy inhibitors, and drug targets. The research hotspots of autophagy and AML in the past 17 years have focused on genetic regulation, autophagy inhibition, and targeted drugs. Chemotherapy resistance and mitochondrial autophagy will be the forefront of research. Conclusion: The gradual increase in the literature on autophagy and AML research and the decline after 2022 could be a result of authors focusing more on the type of research and the quality of the literature. The current research hotspots are mainly genetic regulation, autophagy inhibition, and autophagy-related targeted drugs. In future, autophagy will remain the focus of the AML field, with research trends likely to focus more on AML chemotherapy resistance and mitochondrial autophagy.